Qur'anic Exegesis Study on Moderate Islamic Da'wah at Miftahul Ulum Yahyawiyyah Pati - Fuqohak, Mukhamad Agus Zuhurul (HERMENEUTIK : Jurnal Ilmu al-Qur'an dan Tafsir, 2024)
This study aims to examine the thematic interpretation of moderate Islamic preaching in the Quran at Pondok Pesantren Miftahul Ulum Yahyawiyyah Pati. The issue addressed is the phenomenon of extreme Islamic preaching, which opposes the government, spreads hoaxes, and incites hatred. The method used is thematic interpretation of Quranic verses related to moderate preaching concepts such as wasathiyyah, khoiriyyah, bainiyyah, yusriyyah, hikmah, istiqâmah, and i'tidâl. Field observations, interviews, surveys, and Focus Group Discussions (FGD) were conducted to gather data. The findings reveal that moderate Islamic preaching is characterized by justice, goodness, ease, and centrality between two extremes. The observations at the pesantren showed that the students practice moderate preaching, but there was a need to integrate Islamic and nationalistic values. The FGD provided enlightenment, leading to 98% of students recognizing the importance of integrating religion and nationalism and promoting moderate preaching.